2021
DOI: 10.3389/fonc.2021.783327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Hypofractionated Proton Beam Therapy for Liver Metastasis From Breast Cancer

Abstract: BackgroundFew studies of proton beam therapy (PBT) for patients with liver metastasis from breast cancer (LMBC) are available to date. The aim of the present study was to evaluate the clinical effectiveness of PBT for patients with LMBC.Material and MethodsSeventeen patients with LMBC treated with PBT were included in this study. The median prescribed dose of PBT was 66 GyE (range, 60–80) in 10 fractions, 5 times a week. In patients with LMBC receiving PBT, freedom from local progression (FFLP), progression-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…27 Regarding PBT outcomes, the 1-and 3year OS rates were 88-94.1% and 71.7-73%, respectively, with a median survival time of 39.3 months. 10,11 The summary of clinical results of local treatment for liver metastasis in breast cancer patients is shown in Table 3. A study of prognostic factors predicting survival from rst recurrence in patients with metastatic breast cancer reported that i) size of primary tumor, ii) axillary lymph node status, iii) hormonal receptor status, iv) adjuvant radiotherapy, v) disease free interval, and vi) number of recurrence site were prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Regarding PBT outcomes, the 1-and 3year OS rates were 88-94.1% and 71.7-73%, respectively, with a median survival time of 39.3 months. 10,11 The summary of clinical results of local treatment for liver metastasis in breast cancer patients is shown in Table 3. A study of prognostic factors predicting survival from rst recurrence in patients with metastatic breast cancer reported that i) size of primary tumor, ii) axillary lymph node status, iii) hormonal receptor status, iv) adjuvant radiotherapy, v) disease free interval, and vi) number of recurrence site were prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are few studies that can provide su cient evidence for the treatment of liver metastasis. There are no reports of CIBT, and there are only two reports of PBT on liver metastasis from breast cancer 10,11 In Japan, a nationwide multicenter cohort study on PT was started in May 2016 for all facilities that performed PBT and/or CIBT.…”
Section: Introductionmentioning
confidence: 99%
“…64 A maximum dose of 60 The median progression-free survival (PFS) and OS of 7.9 months and 39.3 months without grade 3 or higher events. 66…”
Section: Discussionmentioning
confidence: 99%
“…The PBT procedures have been described in detail in previous reports [ 26 , 27 , 31 , 32 , 33 , 34 , 35 ]. Patients were immobilized in the supine position with a customized vacuum cushion and underwent contrast-enhanced four-dimensional CT imaging under gating of respiration.…”
Section: Methodsmentioning
confidence: 99%
“…The gross tumor volume (GTV) was defined in average intensity projection CT images at exhalation (gated) phases (i.e., 30% of the entire respiration cycle in each patient) based on available imaging studies, including liver dynamic CT and/or MRI. The internal target volume (ITV) and organs at risk (OARs) were defined to account for the extent and movement of the GTV and each OAR at the exhalation (gated) phases, and the clinical target volume was defined as the ITV with no additional margins [ 25 , 27 , 31 , 32 , 34 , 36 ]. The planning target volume (PTV) was defined as the ITV plus a 5–7 mm margin in all directions.…”
Section: Methodsmentioning
confidence: 99%